The effect of a basic skin care product on the structural strength of the dermo‐epidermal junction: An exploratory, randomised, controlled split‐body trial. Issue 2 (13th June 2021) - El Genedy‐Kalyoncu, Monira; Richter, Claudia; Surber, Christian; Blume‐Peytavi, Ulrike; Kottner, Jan
Abstract: Skin ageing is associated with various structural alterations including a decreased strength of the dermo‐epidermal adhesion increasing the risk for shear type injuries (skin tears). Topical applications of basic skin care products seem to reduce skin tear incidence. The suction blister method leads to the artificial and controlled separation of dermis and epidermis. Therefore, time to blister formation may be used as outcome measuring the strength of dermo‐epidermal adhesion. We conducted an exploratory, randomised, controlled trial with a split‐body design on forearms in healthy female subjects (n = 12; mean age 70.3 [SD 2.1] years). Forearms assigned to the intervention were treated twice daily with petrolatum for 8 weeks. Suction blisters were induced on forearms after 4 and 8 weeks and time to blister formation was measured. Stratum corneum and epidermal hydration were measured and epidermal thickness was assessed via optical coherence tomography. Time to blistering was longer and stratum corneum as well as epidermal hydration was consistently higher in intervention skin areas. We conclude that topical application of basic skin care products may improve mechanical adhesion of the dermo‐epidermal junction and that the parameter "time to blistering" is a suitable outcome to measure dermo‐epidermal adhesion strength in clinical research.